THE METHOD OF MAQĀṢID AL-SYARĪ'AH AS A NEW METHOD OF INTERPRETATION IN THE ISSUE OF CONTEMPORARY MARRIAGE GUARDIANS IN INDONESIA - Nurafni; Andre Khalid; Zul Ikromi (RADJA PUBLIKA, 2025)
This study examines the problems of contemporary wali nikah in Indonesia, where rigid interpretations of classical fiqh clash with modern social realities such as the phenomenon of wali adhal and the increasing independence of women. Using Maqāṣid al-Syarī'ah as a new method of interpretation, this qualitative literature research deconstructs traditional views to reconstruct the role of guardians. The results of the analysis show that the meaning of wali as absolute authority can be contrary to the essential purpose of the shari'a (ḍarūriyyāt). Therefore, ijtihad maqāṣidī was formulated which transforms the role of guardians into protectors and consultants in order to realize benefits.